Body composition affects the response to erythropoiesis-stimulating agents in patients with chronic kidney disease in dialysis. (August 2014) - Vega, Almudena; Ruiz, Caridad; Abad, Soraya; Quiroga, Borja; Velázquez, Kyra; Yuste, Claudia; Aragoncillo, Inés; López Gómez, Juan Manuel
Abstract Background: The response to erythropoiesis-stimulating agents (ESA) in patients with chronic kidney disease (CKD) is variable. The body mass index (BMI) variations can modify the response to ESA. The objective was to assess the effect of body composition on the response to ESA in dialysis patients. Methods: This is an observational cross-sectional study. Prevalent hemodialysis and peritoneal dialysis (PD) patients were selected. In the same day, a single blood test, a body composition analysis using bioimpedance spectroscopy and anthropometric measurements were performed. We collected ESA doses. We analyzed erythropoietin resistance index (ERI). The ERI was calculated dividing the weekly weight-adjusted (kg) dose of ESA (IU) by the hemoglobin level (g/dL). Results: The study was comprised of 218 patients (58% men; age 65 (16) years old; 80% hemodialysis, 20% PD). There was an inverse correlation between ERI and BMI (p = 0.01), fat tissue index (FTI) (p = 0.01) and prealbumin (p = 0.04). We found an independent association between higher ERI levels and lower FTI and prealbumin values. Conclusion: Response to ESA is influenced by body composition. Fat tissue favors the body's response to ESA.